+0  
 
0
165
1
avatar

what is the sum of the square root of -2 and the square root of -18?

Guest Mar 15, 2017
 #1
avatar+87309 
0

sqrt (-2)  + sqrt (-18)  =

 

i * sqrt (2)  + i * sqrt (9 * 2)  =

 

i * sqrt (2)  + i *  sqrt (9) * sqrt (2)   =

 

i * sqrt (2) + i  * 3 *sqrt (2)  =

 

i * sqrt (2)  + 3i * sqrt (2)  =

 

4i *  sqrt (2) =

 

4sqrt (2) i

 

 

cool cool cool

CPhill  Mar 15, 2017

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.